Faire avec les normes de Parcoursup : le cas des réorienté·es - Fanny Bugeja-Bloch; Marie-Paule Couto; Leïla Frouillou; Marion Valarcher
The French platform application for higher education, Parcoursup, increasingly integrates students who want to change their course of studies. This article is based on a qualitative study of applications for an entry in a sociology degree in university. It discusses how Parcoursup imposes administrative norms onto students, and how said norms fail to encompass the non-linear trajectories of students as they change courses. First, the platform's categories are out of touch with those students' trajectories and temporalities. Moreover, application committees do not necessarily read and evaluate the applications in the order the students filled them in, and intended them to be structured. This partly explains why students who change courses are at a disadvantage in admission rankings when compared to new high school graduates.